Relationship between lifestyle and job preference among youths in marginalized communities in Malaysia - Wong, Elizabeth Zu Yee. (2018)
Employment in Malaysia is often set back by the educational and job mismatched. Youth unemployment is basically because of the mismatched between their qualifications to that the job market needs. Based on the Expectancy Theory that focused on job behavior and decision making the study was conducted with the general objective to examine the lifestyles of youth in the marginalized community and its relationship to their job preferences. Specifically the study was conducted to examine, i) to examine the lifestyles of youth in the marginalized community, ii) to examine the job preferences of youth in the marginalized community, iii) to identify the relationship between the lifestyle of youth in the marginalized community and preferences to working in the public organization, iv) to identify the relationship between the lifestyle of youth in the marginalized community and working in the private organization, v) to analyse the most significant factor of lifestyles that affects job preferences. A survey using a set of questionnaire as the instrument for data collection were distributed to 510 respondents mainly in the area of Kerinchi, Seri Kembangan and Klang. The Stratified Sampling Technique was conducted to sample the respondents for the study. The finding of the study shows that the lifestyles of youth affected their job preferences and that they have the tendency to prefer to work in the public organization. However, though the youths in the marginalized community prefer to work in the public organization, based on the lifestyles they are practicing, it leads them to work in the private organization. In terms of the lifestyle domains and the relationship with job preferences, religious and community activities, as well as physical and vocational activities showed a positive relationship towards job preferences of youth in the public organization. On the contrary, religious and community activities, physical and vocational activities as well as highbrow activities showed a positive relationship towards job preferences of youth in the private organization. This can be explained that the marginalized youths were not really involved in media related organizations even though they were engaged in media lifestyles. The regression test using “Enter” method showed that religious and community activity was the best predictor towards job preferences of youth. This was then followed by physical and vocational activities. The study showed that the respondents were practicing a media oriented lifestyle while other dimensions of lifestyles were still being practiced at a moderate level. Therefore, there was likelihood that most of the youth in the marginalized community engaged themselves in the organization based on their religious culture. In general, the lifestyles of youths have a positive relationship on their job preferences which lead towards their desired occupational outcome. This research found that the lifestyles of youths were factor in deciding towards their job preferences. Hence, the findings surprised the Expectancy Theory by Vroom. This research also partially contributed towards the literature in the local context of lifestyles and job preferences.